Effect of Liquidity, Leverage, Inventory Intensity, and Intensity of Fixed Assets on Tax Aggressiveness - Saputra, Rizal; Adriani, Ade; Saprudin, Saprudin (GOVERNORS, 2023)
This study is aimed to know and to prove the influence of liquidity, leverage, inventory intensity, and fixed asset intensity on tax aggressiveness (empirical study on consumer goods companies listed on the Indonesia Stock Exchange for the period 2017-2019). The population in this study were all consumer goods sector companies listed on the Indonesia Stock Exchange (IDX) from 2017 to 2019. The sample in this study was 33 selected companies. The type of data used in this study is secondary data in the form of documentation of the Financial Statements of Consumer Goods Companies listed on the Indonesia Stock Exchange for the period 2017-2019. The method of analysis used in this study is logistic regression analysis. The result of this study showed that inventory intensity had an effect on tax aggressiveness, while liquidity, leverage and fixed asset intensity had no effect on tax aggressiveness in corporate taxpayers registered on the Indonesian stock exchange.